The technology that meets modern human needs – criteria of assessment of smart home system - Gaweł, Dariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The article is a summary of the research conducted for educational purposes with the participation of students from the University of Technology in Lublin in Poland, on the design and use of facilities created as smart home (SH). The increasing availability of smart building equipment systems is associated with their widespread use and reasonable price. New technologies, which are the result of scientific and technological progress, make it possible to use the devices to raise the standard of habitation and use of buildings. The creation of SH facilities nowadays is not only limited to single-family buildings. More and more often we observe smart multi-family and public utility buildings. At the same time, we are aware of the design of energy self-sufficient facilities, which allow us the freedom to build in undeveloped areas.